Temporal Governance and Public Inclusion: A Sociopolitical Study of Civil Service Delivery Innovation in Bali - Hapsari, Komang Heny Tri; Prabawati, Ni Putu Anik (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study examines public service innovation through the "Saturday-Sunday Service Program" initiated by the Population and Civil Registration Office (Disdukcapil) of Badung Regency, Bali, aiming to improve public access to e-KTP (electronic ID card) issuance. The program addresses limited access to administrative services during weekdays, particularly for formal workers, students, and vulnerable groups. Employing a descriptive qualitative approach, the study was conducted at the Disdukcapil office in Badung Regency. Findings indicate that the program fulfills all five key attributes of innovation diffusion theory—relative advantage, compatibility, low complexity, trialability, and observability. It significantly improved public participation in e-KTP registration, achieving a 99.23% coverage rate, the highest in Bali. The initiative has transformed bureaucratic service models into more adaptive, inclusive, and responsive frameworks. The study's novelty lies in its focus on temporal governance—strategic service time management—as a means to reach previously underserved populations. This case demonstrates how need-based public service innovation can enhance administrative effectiveness without compromising regulatory standards. Policy recommendations include operational standardization, strengthening digital infrastructure and human resources, continuous evaluation mechanisms, and nationwide replication. This research contributes to the social sciences by highlighting the roles of time governance, social inclusion, and localized public policy innovation.